Molecular response to combined molecular- and external radiotherapy in head and neck squamous cell carcinoma (HNSCC) - Rassamegevanon, Treewut; Feindt, Louis; Koi, Lydia; Müller, Johannes; Freudenberg, Robert; Löck, Steffen; Sihver, Wiebke; Çevik, Enes; Kühn, Ariane Christel; von Neubeck, Cläre; Linge, Annett; Pietzsch, Hans-Jürgen; et al. (Cancers, 2021)
Combination treatment of molecular targeted and external radiotherapy is a promising strategy and was shown to improve local tumor control in a HNSCC xenograft model. To enhance the therapeutic value of this approach, this study investigated the underlying molecular response. Subcutaneous HNSCC FaDuDD xenografts were treated with single or combination therapy (X-ray: 0, 2, 4 Gy; anti-EGFR antibody (Cetuximab) (un-)labeled with Yttrium-90 (90Y)). Tumors were excised 24 h post respective treatment. Residual DNA double strand breaks (DSB), mRNA expression of DNA damage response related genes, immunoblotting, tumor histology, and immunohistological staining were analyzed. An increase in number and complexity of residual DNA DSB was observed in FaDuDD tumors exposed to the combination treatment of external irradiation and 90Y-Cetuximab relative to controls. The increase was observed in a low oxygenated area, suggesting the expansion of DNA DSB damages. Upregulation of genes encoding p21cip1/waf1 (CDKN1A) and GADD45α (GADD45A) was determined in the combination treatment group, and immunoblotting as well as immunohistochemistry confirmed the upregulation of p21cip1/waf1. The increase in residual γH2AX foci leads to the blockage of cell cycle transition and subsequently to cell death, which could be observed in the upregulation of p21cip1/waf1 expression and an elevated number of cleaved caspase-3 positive cells. Overall, a complex interplay between DNA damage repair and programmed cell death accounts for the potential benefit of the combination therapy using 90Y-Cetuximab and external radiotherapy.
Gesehen am 26.01.2022
This article belongs to the special issue "Cancer radiotherapy"